Epigenetic mechanisms underlie the crosstalk between growth factors and a steroid hormone. Issue 22 (28th September 2017) - Enuka, Yehoshua; Feldman, Morris E.; Chowdhury, Animesh; Srivastava, Swati; Lindzen, Moshit; Sas-Chen, Aldema; Massart, Renaud; Cheishvili, David; Suderman, Matthew J.; Zaltsman, Yoav; Mazza, Chiara A.; Shukla, Kirti; et al.
Abstract: Crosstalk between growth factors (GFs) and steroid hormones recurs in embryogenesis and is co-opted in pathology, but underlying mechanisms remain elusive. Our data from mammary cells imply that the crosstalk between the epidermal GF and glucocorticoids (GCs) involves transcription factors like p53 and NF-κB, along with reduced pausing and traveling of RNA polymerase II (RNAPII) at both promoters and bodies of GF-inducible genes. Essentially, GCs inhibit positive feedback loops activated by GFs and stimulate the reciprocal inhibitory loops. As expected, no alterations in DNA methylation accompany the transcriptional events instigated by either stimulus, but forced demethylation of regulatory regions broadened the repertoire of GF-inducible genes. We report that enhancers, like some promoters, are poised for activation by GFs and GCs. In addition, within the cooperative interface of the crosstalk, GFs enhance binding of the GC receptor to DNA and, in synergy with GCs, promote productive RNAPII elongation. Reciprocally, within the antagonistic interface GFs hyper-acetylate chromatin at unmethylated promoters and enhancers of genes involved in motility, but GCs hypoacetylate the corresponding regions. In conclusion, unmethylated genomic regions that encode feedback regulatory modules and differentially recruit RNAPII and acetylases/deacetylases underlie the crosstalk between GFs and a steroid hormone.